Pengembangan E-Modul Asam Basa Berbasis Discovery Learning Berbantuan Instagram untuk Meningkatkan Motivasi Belajar Peserta Didik - Matakupani, Thilma Tiziana; Aulia, Army; Danial, Muhammad (Program Pasca Sarjana UNM, 2023)
This development research aims to produce a valid, practical, and effective Instagram-assisted Discovery Learning-Based Acid Base E-module. The model used is the ADDIE development model, which consists of five stages, namely the analysis, design, development, implementation, and evaluation. The instrument used for validity test was E- module validation sheet, the practicality test employed teacher and students’ response questionnaire sheet, and the effectiveness test employed learning motivation questionnaire. The sources of validity data were two validators: the practicality used two chemistry teachers and students of grade XI MIPA 2 at SMA Frater Makassar with 32 people. The same method was also used to measure the effectiveness. E-module is declared to be valid based on validation results with a value of 3.87 (very accurate). E-module has met the criteria of practicality because the practicality test is related to (1) a positive teacher’s response questionnaire by 88.39% (very practical) and (2) a positive students’ responses 85.36% (very practical). E-module is stated to be effective based on the results of the learning motivation questionnaire obtained a change in the percentage of learning from 66.38% to 84% and an increase in learning motivation obtained by N-Gain, which is 0.58 (moderate category). Therefore, the results indicate that the Instagram-assisted Discovery Learning-based Acid-Base E-module has valid, practical, and effective qualities.